2020
DOI: 10.1111/1744-7917.12757
|View full text |Cite|
|
Sign up to set email alerts
|

Quality control of the parasitoid wasp Trichogramma brassicae (Hymenoptera: Trichogrammatidae) over 45 generations of rearing on Sitotroga cerealella

Abstract: Trichogramma brassicae (Bezdenko) is an important biological control agent that has been used widely against many lepidopteran pests. Commonly, colonies of Trichogramma are mass reared on factitious hosts such as Sitotroga cerealella (Olivier) over many generations. In this study, we evaluated the quality and performance of a colony of T. brassicae that had been reared for over 45 generations (G) using two-sex life table parameters and parasitism capacity. We found that female adult longevity was significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…69 The life table technique can describe biological parameters, such as parasitoids' survival, development, reproduction, and parasitism, thereby providing the most comprehensive assessment of population dynamics. 28,58,71 In this study, we found that the parasitism performance and life table parameters of T. remus reared on S. litura eggs parasitizing S. frugiperda eggs remained stable. In a similar study, T. remus reared on C. cephalonica eggs for 35-45 generations did not show a significant decrease in parasitism capacity on S. frugiperda eggs, but the number of parasitized eggs was only 59.6-91.1 eggs, which was significantly lower than that of this study.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…69 The life table technique can describe biological parameters, such as parasitoids' survival, development, reproduction, and parasitism, thereby providing the most comprehensive assessment of population dynamics. 28,58,71 In this study, we found that the parasitism performance and life table parameters of T. remus reared on S. litura eggs parasitizing S. frugiperda eggs remained stable. In a similar study, T. remus reared on C. cephalonica eggs for 35-45 generations did not show a significant decrease in parasitism capacity on S. frugiperda eggs, but the number of parasitized eggs was only 59.6-91.1 eggs, which was significantly lower than that of this study.…”
Section: Discussionmentioning
confidence: 55%
“…Numerous studies have demonstrated that long‐term continuous rearing of parasitoids under laboratory conditions leads to poor quality and performance 28,72,73 . Genetic traits of organisms usually change with different rearing environments and conditions, and natural enemy insects are no exception.…”
Section: Discussionmentioning
confidence: 99%
“…Rejuvenating the population by regularly collecting more individuals from natural habitats was a remedy (Ghaemmaghami et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, inbreeding depression may contribute to the gradually decreased fitness of decedents. Rejuvenating the population by regularly collecting more individuals from natural habitats was a remedy (Ghaemmaghami et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have demonstrated that the natal rearing experience of parasitoids may affect their behavioral and physiological characteristics [80][81][82][83]. Ghaemmaghami et al [84] found that laboratory mass-reared colonies of T. brassicae (Hymenoptera: Trichogrammatidae) declined in quality after 15 generations. On the other hand, the long-term rearing of predatory mite Neoseiulus californicus (Acari: Phytoseiidae) on almond pollen positively affected its attributes, including in promoting high survivorship, body size, and fecundity [80].…”
Section: Discussionmentioning
confidence: 99%